Mr Lim Chee Onn appointed as Chancellor of SMU - Singapore Management University (Institutional Knowledge at Singapore Management University, 2019)
The Singapore Management University (SMU) is pleased to announce that Mr Lim Chee Onn (林子安) has been appointed Chancellor (名誉校长) of the University with effect from 1 August 2019. His appointment will be for a term of five years. He was previously the Pro-Chancellor (名誉副校长) of SMU. The positions of Chancellor and Pro-Chancellor are key and important positions within the University structure. Mr Lim, together with the Pro-Chancellor of SMU, Mr Eddie Teo (张赞成), will share the important role of presiding over all major formal University ceremonies, and will officiate at the University’s Commencement and Academic Year Opening Ceremonies.